Indigenous Technical Knowledge (ITK) in Fisheries - B. Nightingale Devi,; S.K. Mishra,; Arpita Sharma,; S.N.Ojha,; N. A. Pawar, (Journal of Agricultural Extension Management, 2025)
This paper examines Indigenous Technical Knowledge (ITK) relating to fisheries. Being practiced in Manipur. The ITKs studied, include fishing methods, fish aggregating devices, fish processing and storage, fish health management, preservation of gears and nets, use of fish waste as manure etc. The 'study suggests that this indigenous knowledge could serve as an entry point to sustainable utilization and management of natural resources, through the exploration and integration of the knowledge into modern technologies. There is need for a suitable linkage mechanism and for documentation and proper utilization of ITKs